Growth of geographic atrophy in the comparison of age-related macular degeneration treatments trials - Grunwald, Juan E; Pistilli, Maxwell; Ying, Gui-Shuang; Maguire, Maureen G; Daniel, Ebenezer; Martin, Daniel F (Ophthalmology (Rochester, Minn.), 2015)
To evaluate the growth of geographic atrophy (GA) during anti-vascular endothelial growth factor (VEGF) therapy. Cohort within a clinical trial. Patients included in the Comparison of Age-related Macular Degeneration Treatments Trials (CATT). Participants were randomly assigned to injections of ranibizumab or bevacizumab and to a 2-year dosing regimen of monthly or pro re nata (PRN) or to monthly for 1 year and PRN the following year. Digital color photographs and fluorescein angiograms at baseline and 1 and 2 years were evaluated for GA, and the total area of GA was measured by 2 graders masked to treatment; differences were adjudicated. Multivariate linear mixed models of the annual change in the square root of the area included baseline demographic, treatment, and ocular characteristics on imaging as candidate risk factors. Geographic atrophy growth rate. Among 1185 participants, 86 (7.3%) had GA at baseline, 120 (10.1%) developed GA during year 1, and 36 (3.0%) developed GA during year 2. Among 194 eyes evaluable for growth, the rate was 0.43 mm/yr (standard error [SE], ±0.03 mm/year). In multivariate analysis, the growth rate was 0.37 mm/year in eyes receiving bevacizumab and 0.49 mm/year in eyes receiving ranibizumab (difference, 0.11 mm/yr; 95% confidence interval [CI], 0.01-0.22; P = 0.03). Growth rate did not differ between eyes treated monthly and PRN (P = 0.85). Eyes with subfoveal choroidal neovascularization (CNV) lesions had a lower growth rate than eyes with nonsubfoveal CNV lesions (difference, 0.12; 95% CI, 0.01-0.22; P = 0.03). Eyes with GA farther from the fovea had higher growth rates by 0.14 (95% CI, 0.01-27) mm/year for every millimeter farther from the fovea. The growth rate was 0.58 mm/year for eyes with predominantly classic lesions, 0.41 mm/year for eyes with minimally classic lesions, and 0.30 mm/year for eyes with occult only lesions (P < 0.01). The growth rate in eyes having a fellow eye with GA was higher by 0.13 mm/year (95% CI, 0.01-0.24; P = 0.03) than in eyes without GA in the fellow eye. Eyes with epiretinal membrane had a higher growth rate than eyes without epiretinal membrane (difference, 0.16; 95% CI, 0.03-0.30; P = 0.02). Geographic atrophy growth depends on several ocular factors. Ranibizumab may accelerate GA growth.